Subjective Birth Experience Predicts Mother–Infant Bonding Difficulties in Women With Mental Disorders - Junge-Hoffmeister, Juliane; Bittner, Antje; Garthus-Niegel, Susan; Goeckenjan, Maren; Martini, Julia; Weidner, Kerstin (Frontiers in Global Women's Health, 2022)
Background: The subjective experience of giving birth to a child varies considerably depending on psychological, medical, situational, relational, and other individual characteristics In turn, it may have an impact on postpartum maternal mental health and family relationships, such as mother-infant bonding. The objective of the study was to evaluate the relevance of the subjective birth experience for mother-infant bonding difficulties in women with mental disorders. Methods: This study used data from N=141 mothers who were treated for postpartum mental disorders in the mother-baby-day unit of the Psychosomatic University Clinic in Dresden, Germany. Patients’ mental status at admission and discharge was routinely examined using a diagnostic interview (SCID I), and standard psychometric questionnaires (e.g., EPDS, BSI, PBQ). Both, the subjective birth experience (SBE; assessed by Salmon’s Item List, SIL) as well as medical complications (MC) were assessed retrospectively by self-report. The predictive value of SBE, MC as well as psychopathological symptoms for mother-infant bonding difficulties were evaluated using logistic regression analyses. Results: About half of this clinical sample (47.2%) reported a negative subjective birth experience; 56.8% of all mothers presented with severe mother-infant bonding difficulties towards the baby. Mothers with bonding difficulties showed not only significantly more depressiveness (EPDS: M=16.6±5.6 vs. 14.4±6.2*), anxiety (STAI: M=57.2±10.6 vs. 51.4±10.6***) and general psychopathology (BSI-GSI: M=1.4±0.7 vs. 1.1±0.6**) compared to women without bonding difficulties, but also a significantly more negative SBE (SIL: M=79.3±16.2 vs. 61.3±22.9***). Moreover, the SBE was the most powerful predictor for bonding difficulties in uni- and multivariate analyses (OR=.96*** [95% CI .94–.98] vs. OR=.96** [95% CI .93–.98]), even when univariate significant predictors (e.g., current psychopathology and medical complications during birth) were controlled. Conclusions: A negative SBE plays an important role for mother-infant bonding in patients with postpartum mental disorders. It needs to get targeted within postpartum treatment, preferably in settings including both, mother and child, to improve distorted mother-infant bonding processes and prevent long term risks for the newborn. Furthermore, the results highlight the importance of focusing on the specific needs of vulnerable women during birth (e.g., emotional safety, good communication and support) and in preparation for it.